PENERAPAN RIL GUNA MENINGKATKAN PRODUKTIVITAS DAN MEMINIMALKAN BIAYA PENYARADAN DI HUTAN TANAMAN RAWA GAMBUT - Sona Suhartana; Yuniawati (Jurnal Penelitian Hasil Hutan, 2015)
Logskiddingtechnique in peatland is different with those practiced in dry land. A well planningisrequired especiallyin the useof the skiddingtool. Since skiddingtakes a large portion of production costs, it is nedeed tocompensate by increasing productivity through implemention of the proper harvestingtechniques. This paper studies the increaseof productivity and minimize production cost by implementing RIL technique at peat swamp plantation forest. The study was conducted on 2012 at the work area of PT Satria Perkasa Agung, in Simpang Kanan District, Pelalawan, Riau Province. Data of skidding cost and productivity were processesed by using tabulation to obtain the mean and then analized using t-test of SPSS 18 software. Results show that: 1. RILSkidding technique in peatland could increase the averageof productivity by 8.37% and decrease the average production cost of 3.93%; 2. The use of proper matting lines on skidding in peat swamp forest can reduce uneffective time about 8.3% equal to 3.66minutes/trip.